(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article is devoted to the study of the characteristics of male and female knowledge in learning English as a second language. We tried to analyse the similarities and differences in English in terms of gender. We came to the conclusion, that the verbal features of the communicative behaviour of men and women very often cause misunderstandings or conflicts between them. Verbal communication is limited only by the linguistic aspect, by which is meant "the manner of speaking in such a way as to be understood.